Features of clinical manifestations, diagnostics and treatment of oral mucosa multi-formed exudative erythema - Ya. A. Lavrovskaya; I. G. Romanenko; O. M. Lavrovskaya; O. N. Postnikova; T. A. Logadyr (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article discusses etiological factors, pathogenesis, features of clinical manifestations, optimization of diagnosis, treatment and prevention of exudative erythema multiforme of the oral cavity. Currently, such pathological changes in the oral cavity are insufficiently studied and remain relevant in modern dentistry. Promising approaches to the successful treatment of this disease involve the implementation of additional examination and joint treatment with related specialists. Numerous studies of domestic and foreign authors demonstrate that special attention is paid to the prevention of re-morbidity of exudative erythema multiforme, aimed at preventing the occurrence of lesions of the oral mucosa.